Degradation of triadimefon and residue levels of metabolite triadimenol: tracing rapeseed from harvesting and storage to household oil processing. (22nd October 2018) - Li, Yinghong; Hu, Jing; Qian, Mingrong; Wang, Qiang; Zhang, Hu
Abstract: BACKGROUND: Triadimefon is a fungicide used in agriculture to control fungal diseases such as sclerotinia sclerotiorum. RESULTS: In field trials, rape plants were sprayed with triadimefon at three different dosages during the flowering period. The degradation of triadimefon and the residue levels of its metabolite, triadimenol, in rapeseed obtained from harvesting, storage, and household oil processing were traced and evaluated. The pesticides were determined by high‐performance liquid chromatography coupled with tandem mass spectrometry (HPLC–MS/MS) at each processing step. Triadimefon degraded completely and only its metabolite, triadimenol, was detected in rapeseed after harvesting. The stability of triadimenol in rapeseed was studied at weekly storage intervals, from 0 to 7 weeks at ambient temperature (25 °C) and freezing temperature (−20 °C), respectively. Storage temperature had an important influence on the residue levels of triadimenol. The processing factor (PF) was defined as the ratio of pesticide residue levels in rapeseed to rapeseed oil levels during household oil processing. The average PF of triadimenol was about 0.96 for a hot pressing technique and 0.88 for a cold pressing technique. CONCLUSION: Different storage conditions and food processing could reduce the pesticide level to a greater or lesser extent. However, it is not easy to eliminate or significantly weaken triadimenol once triadimefon has degraded completely. © 2018 Society of Chemical Industry